2019
DOI: 10.1152/ajplung.00381.2018
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled combination of sildenafil and rosiglitazone improves pulmonary hemodynamics, cardiac function, and arterial remodeling

Abstract: Currently, dual- or triple-drug combinations comprising different vasodilators are the mainstay for the treatment of pulmonary arterial hypertension (PAH). However, the patient outcome continues to be disappointing because the existing combination therapy cannot restrain progression of the disease. Previously, we have shown that when given as a monotherapy, long-acting inhaled formulations of sildenafil (a phosphodiesterase-5 inhibitor) and rosiglitazone (a peroxisome proliferator receptor-γ agonist) ameliorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Nevertheless, the quest for novel therapeutics exploiting PPAR‐γ signalling continues. An inhaled therapy combining sildenafil and rosiglitazone was successfully applied in rats with PH in a recently published study (Rashid, Nozik‐Grayck, McMurtry, Stenmark, & Ahsan, 2019).…”
Section: Novel Treatment Options Targeting Specific Pathways In Pahmentioning
confidence: 99%
“…Nevertheless, the quest for novel therapeutics exploiting PPAR‐γ signalling continues. An inhaled therapy combining sildenafil and rosiglitazone was successfully applied in rats with PH in a recently published study (Rashid, Nozik‐Grayck, McMurtry, Stenmark, & Ahsan, 2019).…”
Section: Novel Treatment Options Targeting Specific Pathways In Pahmentioning
confidence: 99%
“…However, other investigators found that oral sildenafil at 50 mg/kg once daily for 14 days did provide positive pulmonary vascular remodeling with reduced percentage of muscularization, reduced medial hypertrophy and reduced number of occluded small arteries 17 . More recently, beneficial arteriolar remodeling was also present with chronic inhaled sildenafil in short or long acting formulations in the same model 18 . Adrenomedullin (AM) is a 52 amino acids peptide with vasodilator and anti-proliferative actions.…”
Section: Discussionmentioning
confidence: 86%
“…Sildenafil is a highly selective phosphodiesterase-5 inhibitor, which can enhance the cGMP pathway, ultimately affect the synthesis and release of vasoactive factor NO, and regulate the level of free Ca 2þ in cells, resulting in vascular dilatation and reduction of pulmonary artery pressure (Gao et al 2020). It has been proven that sildenafil alone or in combination with other drugs has a certain effect on various types of pulmonary hypertension, and its price is cheaper than prostacyclin drugs and endothelin receptor antagonists (Rashid et al 2019). Therefore, its clinical application prospects, especially the effect of combined use with other drugs is compelling.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven that sildenafil alone or in combination with other drugs has a certain effect on various types of pulmonary hypertension, and its price is cheaper than prostacyclin drugs and endothelin receptor antagonists (Rashid et al. 2019 ). Therefore, its clinical application prospects, especially the effect of combined use with other drugs is compelling.…”
Section: Discussionmentioning
confidence: 99%